2015
DOI: 10.1002/ana.24372
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hydrogen sulfide involvement in amyotrophic lateral sclerosis

Abstract: This study unravels H2 S as an astroglial mediator of motor neuron damage possibly involved in the cellular death characterizing ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 77 publications
(202 reference statements)
3
58
0
4
Order By: Relevance
“…This stimulation is involved in induction of hippocampal long‐term potentiation, a synaptic model of memory . Recently, involvement of H 2 S as an astroglial mediator of motor neuron damage in Amyotrophic lateral sclerosis (ALS) has been shown . It has been demonstrated that Hcy levels are significantly increased in plasma and cerebrospinal fluid of patients with ALS .…”
Section: Introductionmentioning
confidence: 99%
“…This stimulation is involved in induction of hippocampal long‐term potentiation, a synaptic model of memory . Recently, involvement of H 2 S as an astroglial mediator of motor neuron damage in Amyotrophic lateral sclerosis (ALS) has been shown . It has been demonstrated that Hcy levels are significantly increased in plasma and cerebrospinal fluid of patients with ALS .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] These effects result in a series of extrapyramidal symptoms including cellular, molecular, and behavioral abnormalities. 36,37 When microglia are injured, they affect cellular functions and implicate in the cellular damage, or even lead to oxidative stress and mitochondrial dysfunction. [29][30][31] Microglia, as resident immunocompetent and phagocytic cells, can regulate and maintain the microenvironment of the central nervous system (CNS), and identify signals in response to CNS injury.…”
Section: Introductionmentioning
confidence: 99%
“…19,20,22,23 The toxicity of ATR in the dopaminergic system has been confirmed both in vivo 22,23,28 and in vitro. 37,38 In contrast, activated microglia produce inflammatory mediators that contribute to neurodegeneration. 32 Microglia are present in a resting state in the normal brain, where they release anti-inflammatory and trophic molecules to promote neuronal survival.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S в патогенезе БАС. У пациентов со спорадическим БАС установлено существенное повышение концентрации H 2 S в СМЖ [10,22], которое сопровождается слабой корреляционной взаимосвязью со стадией заболевания. Относительно более высокий уровень H 2 S в ликворе отмечается преимущественно в женской популяции пациентов; между содержанием H 2 S и «местом проявления» симптомов заболевания прослеживается определенная связь; для пациентов с «БАС конечностей» характерна значительно более высокая концентрация H 2 S в СМЖ, чем для пациентов с «бульбарным БАС» [22,23].…”
unclassified
“…При моделировании семейного БАС на мышах линии SOD1G93A обнаружено увеличение уровня H 2 S в спинном мозге, стволе и коре головного мозга [22]. Аналогичное увеличение содержания H 2 S отмечалось не только в тканях, но и в среде культуры клеток спинного мозга с мутацией SOD1G93A, моделировавшей семейный БАС [10,23]. Как и в случае с разнополыми пациентами, у самок трансгенных мышей наблюдалась более высокая концентрация H 2 S [22].…”
unclassified